2021
DOI: 10.3390/ijms22179121
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts in Conversation with Tumor Cells in Endometrial Cancers: A Partner in Crime

Abstract: A tumor cell carrying characteristic genomic alteration(s) exists within its host’s microenvironment. The tumor microenvironment (TME) renders holistic support to the tumor via cross-talk between tumor cells and three components of TME, immune components, vascular components, and fibroblast components. The tempero-spatial interaction of tumor cells with its microenvironment is the deterministic factor for tumor growth, progression, resistance to therapy, and its outcome in clinics. TME (1) facilitates prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Endometrial cancer is the six most commonly occurring cancer in women worldwide (Ferlay et al, 2021). Elevated levels of pro-inflammatory cytokines pose a major risk in endometrial cancer development (Dossus et al, 2013), and a fibrotic microenvironment appears to contributes to endometrial tumor aggressiveness and drug resistance (Pradip et al, 2021). The risk of developing endometrial carcinomas may also be shaped by events that alter the number of menstrual cycles, such as oral contraception usage, number of pregnancies, and age of menarche and menopause (Havrilesky et al, 2013; Iversen et al, 2017; Michels et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer is the six most commonly occurring cancer in women worldwide (Ferlay et al, 2021). Elevated levels of pro-inflammatory cytokines pose a major risk in endometrial cancer development (Dossus et al, 2013), and a fibrotic microenvironment appears to contributes to endometrial tumor aggressiveness and drug resistance (Pradip et al, 2021). The risk of developing endometrial carcinomas may also be shaped by events that alter the number of menstrual cycles, such as oral contraception usage, number of pregnancies, and age of menarche and menopause (Havrilesky et al, 2013; Iversen et al, 2017; Michels et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li and his colleagues reported that Treg has a higher infiltration level in in the peripheral blood of EC cases than healthy control [ 30 ]. Also, cancer-associated fibroblast (CAF) is a major cell subpopulation in TME which affects the biological behavior of EC through CAF-tumor cell cross-talk [ 31 ]. Furthermore, CAF extracted from EC tissues could secrete IL-6, which subsequently boosts c-Myc expression to accelerate EC growth [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Truong | URNCST Journal (2022): Volume 6, Issue 8 Page 2 of 7 DOI Link: https://doi.org/10.26685/urncst.346 cell, including influencing the proliferation of the tumour cell through multiple signalling pathways [3], such as the TGF-β signalling pathway.…”
Section: Research Protocol Open Accessmentioning
confidence: 99%
“…A particular cell of interest are cancerassociated fibroblasts (CAFs) which play a significant role in the growth and maintenance of cancers primarily through paracrine signalling and modification of the extracellular matrix [2]. In the EC TME, CAFs promote tumour proliferation, migration and invasion into neighbouring cells, tumorigenesis, and development of drug resistance [3]. Crosstalk between the tumour cells and CAFs initiates and sustains different functions of the endometrial tumour…”
Section: Introductionmentioning
confidence: 99%